KONTRIBUSI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 PADANG PANJANG - Sari, Anggun Permata; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three. First, describe the mastery of the vocabulary environment in class VII Padang Panjang Middle School 2. Second, describe the text writing skills of class VII students at Padang Panjang Middle School 2. Third, describe the contribution of mastery of environmental vocabulary to the text writing skills of seventh grade students at Padang Panjang Middle School 2. This type of research is quantitative with descriptive method. The design used in this study is the design contribution. The results of this study are three. First, mastery of vocabulary in class VII Padang Panjang SMP Negeri 2 has good qualifications (B) with an average score of 78.48. Second, the text writing skills of class VII students of Padang Panjang Middle School 2 are in good qualification (B) with an average score of 76.49. Third, there is a contribution to mastery of environmental vocabulary on the text writing skills of seventh grade students at Padang Panjang Middle School 2 at 59.44%.Â Kata kunci: Kontribusi, Kosakata Bidang Lingkungan, Menulis, Teks Deskripsi